Transition To Adult Care: Exploring Factors Associated With Transition Readiness Among Adolescents And Young People In Adolescent ART clinics in Uganda - Mbalinda, Scovia Nalugo; Kitaka, Sabrina Bakeera; Lusota, Derrick Amooti; Musoke, Philippa; Nyashanu, Mathew; Kaye, Dan Kabonge (PloS one, 2021)
Transition readiness refers to a client who knows about his/her illness and oriented towards future goals and hopes, shows skills needed to negotiate healthcare, and can assume responsibility for his/ her treatment, and participate in decision-making that ensures uninterrupted care during and after the care transition to adult HIV care. There is a paucity of research on effective transition strategies. This study explored factors associated with adolescent readiness for the transition into adult care in Uganda.A cross-sectional study was conducted among 786 adolescents, and young people living with HIV randomly selected from 9 antiretroviral therapy clinics, utilizing a structured questionnaire. The readiness level was determined using a pre-existing scale from the Ministry of Health, and adolescents were categorized as ready or not ready for the transition. Bivariate and multivariate analyses were conducted.A total of 786 adolescents were included in this study. The mean age of participants was 17.48 years (SD = 4). The majority of the participants, 484 (61.6%), were females. Most of the participants, 363 (46.2%), had no education. The majority of the participants, 549 (69.8%), were on first-line treatment. Multivariate logistic regression analysis found that readiness to transition into adult care remained significantly associated with having acquired a tertiary education (AOR 4.535, 95% CI 1.243–16.546, P = 0.022), trusting peer educators for HIV treatment (AOR 16.222, 95% CI 1.835–143.412, P = 0.012), having received counselling on transition to adult services (AOR 2.349, 95% CI 1.004–5.495, P = 0.049), having visited an adult clinic to prepare for transition (AOR 6.616, 95% CI 2.435–17.987, P = < 0.001) and being satisfied with the transition process in general (AOR 0.213, 95% CI 0.069–0.658, P = 0.007).The perceived readiness to transition care among young adults was low. A series of individual, social and health system and services factors may determine successful transition readiness among adolescents in Uganda. Transition readiness may be enhanced by strengthening the implementation of age-appropriate and individualized case management transition at all sites while creating supportive family, peer, and healthcare environments.